The benefits of family-centered care for parental self-efficacy and psychological well- being in parents of children with cancer - Salvador, Ágata (2022)
Objectives The purpose of this study was to examine the direct and indirect links between the perception of family-centeredcare (FCC) and psychological well-being via the perceived self-efﬁcacy of parents of children with cancer. This study alsosought to identify the potential moderators of these links (treatment status and patient age).Methods This cross-sectional study was conducted at the pediatric oncology wards of two Portuguese public hospitals. Theconsecutive sample comprised 251 parents (87.6% mothers) of children/adolescents (8−20 years old) diagnosed with cancer.Participants completed self-report questionnaires measuring their perception of family-centered care (family-centered ser-vices and providing general information), perceived self-efﬁcacy (regarding healthcare and parenting role) and psychologicalwellbeing.Results Results from the Structural Equation Modeling suggested that parents’perception of FCC was indirectly, but notdirectly, linked to psychological well-being via perceived self-efﬁcacy. Multi-group analyses suggested that this mediationmodel was valid across treatment status (on vs. off-treatment) and patient age groups (children vs. adolescents).Conclusions These ﬁndings highlighted that, through the implementation of FCC, healthcare professionals may promoteparents’perceived self-efﬁcacy and, consequently, their psychological well-being. Results also suggest that FCC mayequally operate on parents’psychosocial functioning, regardless of treatment status or patient age. Overall, our ﬁndingsreinforced the beneﬁts of FCC practices in pediatric oncology wards.